2004
DOI: 10.1002/art.20005
|View full text |Cite
|
Sign up to set email alerts
|

WISP3‐dependent regulation of type II collagen and aggrecan production in chondrocytes

Abstract: Objective. WISP3 (Wnt-1-inducible secreted protein 3) is a member of the CCN (connective tissue growth factor, cysteine-rich 61, nephroblastoma overexpressed) family of connective tissue growth factors. WISP3 mutations have been linked to progressive pseudorheumatoid dysplasia (PPRD). The present study was conducted to investigate whether WISP3 is responsible for the expression of cartilage-specific molecules.Methods. WISP3 expression in human cartilage was assessed by immunostaining with anti-WISP3 antibody. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…Reactions were run in triplicate with 40 cycles of amplification on an ABI Prism 7000 real-time PCR machine (Applied Biosystems, Foster City, CA). The sequences of primers used were as follows: aggrecan, sense (5Ј-AGAATCCACCACCA-CCAG-3Ј) and antisense (5Ј-ATGCTGGTGCTGATGACA-3Ј); TATA box-binding protein, sense (5Ј-TGCACAGGAG-CCAAGAGTGAA-3Ј) and antisense (5Ј-CACATCACAGC-TCCCCACCA-3Ј) (28); collagen II, sense (5Ј-TGCTGCCC-AGATGGCTGGAGGA-3Ј) and antisense (5Ј-TGCCTTGA-AATCCTTGAGGCCC-3Ј) (29); Sox9, sense (5Ј-CACAC-TACAGCCCCTCCTAC-3Ј) and antisense (5Ј-CCTCCTC-AAGGTCGAGTGAG-3Ј) (30). The expression levels of aggrecan, collagen II, and Sox9 mRNA were normalized relative to the expression of TATA box-binding protein measured in parallel samples.…”
Section: Methodsmentioning
confidence: 99%
“…Reactions were run in triplicate with 40 cycles of amplification on an ABI Prism 7000 real-time PCR machine (Applied Biosystems, Foster City, CA). The sequences of primers used were as follows: aggrecan, sense (5Ј-AGAATCCACCACCA-CCAG-3Ј) and antisense (5Ј-ATGCTGGTGCTGATGACA-3Ј); TATA box-binding protein, sense (5Ј-TGCACAGGAG-CCAAGAGTGAA-3Ј) and antisense (5Ј-CACATCACAGC-TCCCCACCA-3Ј) (28); collagen II, sense (5Ј-TGCTGCCC-AGATGGCTGGAGGA-3Ј) and antisense (5Ј-TGCCTTGA-AATCCTTGAGGCCC-3Ј) (29); Sox9, sense (5Ј-CACAC-TACAGCCCCTCCTAC-3Ј) and antisense (5Ј-CCTCCTC-AAGGTCGAGTGAG-3Ј) (30). The expression levels of aggrecan, collagen II, and Sox9 mRNA were normalized relative to the expression of TATA box-binding protein measured in parallel samples.…”
Section: Methodsmentioning
confidence: 99%
“…Prior investigations revealed that WISP3 promotes expression of the cartilage specific proteins collagen-II and aggrecan, controls the accumulation of reactive oxygen species (ROS) and regulates metalloprotease expression, corroborating that WISP3 sustains cartilage differentiation in vivo (Sen et al, 2004;Davis et al, 2006;Miller and Sen, 2007;Baker et al, 2012). Other studies have reported that WISP3 interacts with BMP and components of the Wnt1 signaling pathway including LRP6 and Fz8 (Nakamura et al, 2007).…”
mentioning
confidence: 73%
“…The disease manifestations linked to WISP3 mutations suggest that WISP3 is required for proper skeletal growth and maintenance of cartilage integrity (Hurvitz et al, 1999;Delague et al, 2005). Although the detailed molecular mechanism of the action of WISP3 is not resolved yet, existing functional studies justifying a role of WISP3 in skeletal development and cartilage maintenance are in accordance with the clinical and radiographic picture associated with WISP3 mutations (Hurvitz et al, 1999;Sen et al, 2004;Delague et al, 2005;Lamb et al, 2005;Davis et al, 2006;Miller and Sen, 2007;Nakamura et al, 2007;Baker et al, 2012;Garcia Segarra et al, 2012).…”
mentioning
confidence: 96%
“…The C57BL/6 and MLg lung fibroblasts (8!10 3 cells per well) were cultured in 96-well flat-bottomed tissue plates in RPMI1640 supplemented with 10% FBS, and then serum-starved in medium containing 0.1% FBS overnight (19,20,22) [19,27,28]. Next, the cells were treated with various doses (1 to 200 ng/ml) of CCN6, and PDGF-BB (10 ng/ml) as a positive control for 72 hours, and labeled with 3 H -thymidine deoxyribose (TdR) (6.7 Ci/mmol ; Amersham Corp., Arlington Heights, IL) at 1 μCi/ well for the final 18 hours.…”
Section: Proliferation Assaymentioning
confidence: 99%
“…The ECM plays a vital early role in the repair process, orchestrating the modulation and transition of cell phenotype and function (26). It has been shown that CCN6 stimulates collagen type II, aggrecan, and superoxide dismutase expression and activity in chondrocytes (27,28). To investigate whether CCN6 affects on ECM production, we treated C57BL/6 cells with CCN6 and examined the mRNA expression of fibronectin and type I collagen by real-time RT-PCR analysis.…”
Section: Effects Of Ccn6 Protein On the Proliferation And Expression mentioning
confidence: 99%